ZATWIERDZENIE I STWIERDZENIE WYKONALNOŚCI UGODY W KONTEKŚCIE ZASADY POUFNOŚCI MEDIACJI - Kierska, Maria; Marek, Tomasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Mediation is one of the most popular and developed alternative dispute resolution methods. Especially in the western European countries and the USA. In contrast, in Poland mediation still stays an undiscovered way of problem solving, due to the lack of both clear statutory regulations and wellfounded judicature on mediation’s core elements and ground rules. One of the fundamental axioms of mediation is the importance of confidentiality. It allows parties to fully engage in the process. The confidentiality rule was designed to give all participants the assurance that nothing said or done in the mediation process, can be further disclosed, exploited or used (e.g. in the court proceedings). Nonetheless, even though mediated settlement, as a result od both parties consensus, is in most cases abide by the parties, there might be cases when one of the parties questions its validity, and attempts to resist enforcement of the agreement. This article deals with both grounds for possible defenses, such as the dispute about existence or content of the mediated settlement, as well as the contract defenses (i.a. fraud, duress). In that aspect, development of the mediation process, parties’ behaviour and standpoints are often crucial to evaluating the validity of the agreement, yet this evidence would undermine the rule of mediation confidentiality. This article aims to explore competing policies between enforcing mediated settlement and maintaining the confidentiality of the mediation process, in polish and common law system.